Potent inhibition of OKT3-induced T cell proliferation and suppression of CD147 cell surface expression in HeLa cells by scFv-M6-1B9 - Intasai N. (2014)
CD147, a multifunctional type I transmembrane glycoprotein, has been implicated in various physiological and pathological processes. It is involved in signal transduction pathways and also plays a crucial role in the invasive and metastatic activity of malignant tumor cells. Diminished expression of this molecule has been shown to be beneficial in suppression of tumor progression. In a previous study, we generated and characterized a recombinant antibody fragment, scFv, which reacted specifically to CD147. In the present study, we further investigated the biological properties, function and the effect of generated scFv on CD147 expression. The in vitro study showed that soluble scFv-M6-1B9 produced from E. coli HB2151 bound to CD147 surface molecule and inhibited OKT3-induced T cell proliferation. Furthermore, soluble lysate of scFv-M6-1B9 from 293A cells, transduced with a scFv-M6-1B9 expressing adenovirus vector, recognized both recombinant and native CD147. These results indicate that scFv-M6-1B9 binds with high efficiency and specificity. Importantly, scFv-M6-1B9 intrabody reduced the expression of CD147 on the cell surface of HeLa cells suggesting that scFv-M6-1B9 is biologically active. In conclusion, our present study demonstrated that scFv-M6-1B9 has a great potential to target both the intracellular and the extracellular CD147. The generated scFv-M6-1B9 may be an effective agent to clarify the cellular function of CD147 and may aid in efforts to develop a novel treatment in various human carcinomas. © 2009 Elsevier GmbH.